Case reportExternal iliac artery pseudo-stenosis associated with catheterization: report of two cases - Karapinar, Hekim; Gül, İbrahim; Küçükdurmaz, Zekeriya; Gümrükçüoglu, Hasan Ali; Yilmaz, Ahmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
In invasive cardiology practices, the most commonly used vascular access site is the femoral artery. Atherosclerotic stenoses on the femoral and iliac arteries create difficulties in these practices. Vasospasm rarely occurs on large arteries like these. This paper reports stenosis encountered during coronary angiography on iliac arteries in 2 patients. The stenoses caused difficulties for guidewire and catheter insertion in catheterization. In the revisualization of these arteries at the next session, the stenoses had disappeared, but the arteries were tortuous. The patients did not have peripheral ischemia signs previously, nor did they appear after the procedure. These transient stenoses might have occurred due to vasospasm and the accordion effects caused by the guidewire and/or catheter.